Statistical model calculations of 72,73Ge(n,p) and 72,74Ge(n,α) reactions on natural Ge - Galanopoulos, S.; Vlastou, R.; Demetriou, P.; Kokkoris, M.; Papadopoulos, C. T.; Perdikakis, G.; Serris, M. (HNPS Advances in Nuclear Physics, 2020)
Systematic experimental and theoretical investigations of the 72,73Ge(n,p)72,73 Ga and 72,74Ge(n,α)69,71Znm reaction cross sections are presented in the energy range from thresh- old to about 17 MeV neutron energy. The above reaction cross sections were measured from 8.8 to 11.4 MeV by using the activation method, relative to the 27Al(n,α)24Na refer- ence reaction. The quasi-monoenergetic neutron beams were produced via the 2H(d,n)3He reaction at the 5 MV VdG Tandem T11/25 accelerator of NCSR “Demokritos”. Statisti- cal model calculations using the code EMPIRE-II (version 2.19) taking into consideration pre-equilibrium emission were performed on the data measured in this work as well as on data reported in literature.